Osteoarthrosis of the hip in women and its relation to physical load at work and in the home. Issue 5 (1st May 1997) - Vingård, Eva; Alfredsson, Lars; Malchau, Henrik
Abstract : OBJECTIVES: The aim of this case referent study was to investigate the relation between physical workload and osteoarthrosis of the hip in women. METHODS: The study base comprised all women of ages 50-70 years, living in five counties and four towns in Sweden 1991-1994. Cases (n=230), who had undergone total hip replacement for primary osteoarthrosis of the hip were identified by means of the Swedish National Register of Total Hip Replacements, and the referents (n=273) were women without hip problems randomly selected from the study base. All women were interviewed about state of health, smoking habits, occupational history, work in the home, sports activities, etc. Each subject's history of occupational work and work in the home up to the age of 50 was divided into periods within each of which the work tasks were similar, and a questionnaire for each such period was filled in by the participants. On the basis of information given by the referents, the women were classified as having had low, medium, and high exposure to different factors. Relative risks (RRs) and 95% confidence intervals (CI) were calculated. RESULTS: Physically demanding tasks at work and in the home were associated with increased RRs of osteoarthrosis of the hip in those with high exposure compared with the low exposure group. A RR in the range of 2 or higher was found for those who frequently jumped or moved between different levels (RR=2.1, CI 1.9, 4.2), who frequently climbed stairs (RR=2.1, CI 1.2, 3.6), and who had physically demanding tasks outside occupational life (RR=2.3, CI 1.5, 3.6). The highest RR (RR=4.3, CI 1.7, 11.0) was found for those exposed to high physical loads both at work and during sports activities. CONCLUSION: High physical loads at work and in the home up to the age of 50 seem to be risk factors for development of severe osteoarthrosis of the hip in women.